Blossom-end rot of pears : systemic infection of flowers and immature fruit by Botrytis cinerea - De Kock, Selma L.(Selma Louisa) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1990.